Criminal justice response in Cape Verde: understanding punishment severity in case of gender-based violence against women - Mendes Rodrigues, Edília (International journal of law, crime and justice, 2024)
Gender-based violence (GBV) is the subject of a unique statute and has been defined as a criminal offence requiring criminal intervention in Cape Verde since 2011. However, while numerous studies have been conducted on the sentencing outcomes of GBV against women, this phenomenon has received little to no attention in the African context, particularly in Cape Verde. This study examines 72 court cases involving heterosexual couples with female victims and male offenders. Data were collected using Punishment Severity and Psychologization Index (Secondary Criminalization) Revised - PSPI(SC) - R. The results revealed that the severity of punishment in GBV against women in Cape Verde on average is lenient and judges did not consider support from behavioral practitioners in their decisions. Additionally, correlation analysis showed that level of education and criminal record were correlated with the punishment severity index (PSI). To determine the strength and to what extent these two factors explain the variation in PSI, a multiple regression analysis was carried out. This indicated that (i) the lower the offender's level of education, the higher the severity of punishment and (ii) offenders with criminal records have an average harsher sentence than their respective counterparts who had no prior criminal record. The study highlights the need for a more rigorous and informed approach to GBV cases against women in Cape Verde, balancing punitive measures with the inclusion of behavioral practitioner support in judicial decisions to better protect victims and reduce recidivism among offenders.